Bioconversion of a ganoderic acid 3-hydroxy-lanosta-8, 24-dien-26-oic acid by a crude enzyme from Ganoderma lucidum. (August 2020) - Cai, Siqin; Xiao, Han; Wang, Xiaozheng; Lin, Shuangjun; Zhong, Jian-Jiang
Graphical abstract: Highlights: Post-modification of 3-hydroxy-lanosta-8, 24-dien-26 oic acid (HLDOA) was found. The conversion product of HLDOA was 3-oxo-lanosta-8, 24-dien-26 oic acid (OLDOA). The work is useful to biomanufacture and pathway elucidation of GAs. Abstract: Ganoderic acids (GAs) are oxygenated lanostane-type triterpenoids from the traditional medicinal mushroom Ganoderma lucidum and of significant biological activities. Although a ganoderic acid 3-hydroxy-lanosta-8, 24-dien-26-oic acid (HLDOA) was found to be biosynthesized from lanosterol, further post-modification of HLDOA is yet unclear. In this work, by using HLDOA as the substrate and a crude enzyme from G. lucidum as the biocatalyst, we observed a new peak in liquid chromatography from the reaction system. The product was purified and identified to be 3-oxo-lanosta-8, 24-dien-26-oic acid (OLDOA), which may be converted from HLDOA by a putative dehydrogenase of G. lucidum . The work is useful to future manufacture of GAs as well as their biosynthetic pathway elucidation.